\(\frac{a}{3b}=\frac{b}{3c}=\frac{c}{3d}=\frac{d}{3a}=\frac{a+b+c+d}{3a+3b+3c+3d}=\frac{1}{3}.\)
\(\Rightarrow\frac{a}{3b}=\frac{1}{3}\Rightarrow a=b\)
\(\Rightarrow\frac{b}{3c}=\frac{1}{3}\Rightarrow b=c\)
\(\Rightarrow\frac{c}{3d}=\frac{1}{3}\Rightarrow c=d\)
Vậy, a=b=c=d đpcm.
Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
\(\frac{a}{3b}=\frac{b}{3c}=\frac{c}{3d}=\frac{d}{3a}=\frac{a+b+c+d}{3b+3c+3d+3a}=\frac{a+b+c+d}{3\left(a+b+c+d\right)}=\frac{1}{3}.\)
\(\Rightarrow\)
\(\frac{a}{3b}=\frac{1}{3}\Rightarrow\frac{a}{b}=1\)(1)
\(\frac{b}{3c}=\frac{1}{3}\Rightarrow b=c\)(2)
\(\frac{c}{3d}=\frac{1}{3}\Rightarrow c=d\)(3)
\(\frac{d}{3a}=\frac{1}{3}\Rightarrow d=a\)(4)
Từ (1)(2)(3)(4) suy ra a= b=c=d(dpcm)